2017
DOI: 10.1002/acp.3314
|View full text |Cite
|
Sign up to set email alerts
|

Adult Eyewitness Memory for Single Versus Repeated Traumatic Events

Abstract: Reports from individuals who have witnessed multiple, similar emotional events may differ from reports from witnesses of only a single event. To test this, we had participants (N = 65) view a video of a road traffic accident. Half of the participants saw two additional (similar) aversive films. Afterwards, participants filled out the Self-Administered Interview on the target film twice with an interval of 1 week. Participants who saw multiple similar films were less accurate in recalling details from the targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 36 publications
5
44
1
Order By: Relevance
“…The results of the current study are in contrast to what was predicted based on research examining event repetition and exposure duration (e.g., McNichol et al, 1999;Theunissen et al, 2017). Research on event repetition has demonstrated that recall of event details increases after being exposed to the same event several times in comparison to one exposure (McNichol et al, 1999).…”
Section: Recall Of Familiar-strangerscontrasting
confidence: 99%
See 3 more Smart Citations
“…The results of the current study are in contrast to what was predicted based on research examining event repetition and exposure duration (e.g., McNichol et al, 1999;Theunissen et al, 2017). Research on event repetition has demonstrated that recall of event details increases after being exposed to the same event several times in comparison to one exposure (McNichol et al, 1999).…”
Section: Recall Of Familiar-strangerscontrasting
confidence: 99%
“…Similarly, this explains why the participants who were repeatedly exposed to similar events (but which contained differing verbatim details) in Theunissen et al (2017) showed decreased recall accuracy compared to the group who only witnessed one event. In this study the meaning of the repeated events was the same, but the verbatim details differed, and thus gist memories were retrieved.…”
Section: Exposure Durationmentioning
confidence: 91%
See 2 more Smart Citations
“…Most of our autobiographical memory involves multiple experiences with familiar events. Research demonstrates that recalling a single instance from a series of familiar, or similar, activities is difficult for both adults and children (e.g., Means & Loftus, ; Price, Connolly, & Gordon, ; Theunissen, Meyer, Memon, & Weinsheimer, ). Hints to the origin of this difficulty can be found in the literature that demonstrates that both prior knowledge (proactive interference; Keppel & Underwood, ) and new experiences (retroactive interference; Barnes & Underwood, ) can influence memory of a familiar happening.…”
Section: Introductionmentioning
confidence: 99%